The innovative activity development of higher educational institutions - Romanova, Anzhela V.; Polevaya, Marina V.; Khammatova, Rina S.; Sokolovskaya, Irina E.; Platonova, Elena V.; Kolosova, Valeria V. (Opción, 2020)
The paper presents the results of a study of the problem of the innovative activity development carried out by higher educational institutions in the field of high technologies and commercialization of scientific developments via comparative qualitative research methods. As a result, the introduction of the Model of scientific and educational transfer of technology into the system of higher professional education will make it possible to develop the innovative activity of higher education institutions. In conclusion, the high quality of personnel training is maintained by the use of a multi-level system of evaluating knowledge, skills; engaging highly-qualified Russian and foreign teachers.